A landscape view on antimicrobial resistance pattern of Acinetobacter baumannii and Vibrio cholerae in hospital wastewater and adjacent household water - Morshed, Sumaiya; Khan, Shadman Sakib (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.